Kecanduan Mahasiswa Terhadap Perjudian Slot Online - Febby Nabila (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2024)
The development of technology and the Internet that is happening now is very rapid so that it causes many phenomena that occur in public life. The positive impact given by technology is very felt, namely technology and the internet facilitate daily work making communication very easy now the National Exam is carried out online on a computer, then along with the magnitude of the positive impact provided by the internet also raises a large negative impact also for example online slot gambling among students. Higher education, which should be an aspect of development in the country, instead committed deviant actions that violated the ITE Law which regulates technology and the internet. From the many research results that have been done, it can be concluded that doing online slot gambling is the result of the learning process and involvement carried out by students such as looking for a trusted online slot gambling site, having an online slot gambling account, playing online slot gambling, disbursing the money that has been earned. Then the motive of students playing online gambling is Because Motive: the influence of the social environment, economic factors, the desire to get something. In order to motive: increase association, addicted to playing online gambling, online gambling is safer, run out of money.